A new test for superficialis flexor tendon function - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2000)
Diagnosis of flexor digitorum superficialis tendon injury is difficult if the profundus tendon functions properly. A new test, called the DIP extension test, to diagnose isolated flexor digitorum superficialis tendon injuries is described. The test is particularly useful for the index finger. During the test the patient is asked to flex the proximal interphalangeal joint of the injured finger while this finger is in a precision pinch position with the thumb. The distal interphalangeal (DIP) joint normally has to go in hyperextension after this action. Inability to hyperextend the DIP joint confirms a superficialis tendon injury. Fifteen isolated superficialis tendon injuries in 10 patients were evaluated with the DIP extension test. Nine of these patients were later explored and the diagnosis was confirmed in all patients.